Nexus between Financial and Technology Inclusion, Remittances and Trade Openness vis-à-vis growth: A study of Nepal - Kumar, Ronald Ravinesh (Economic Journal of Nepal, 2014)
Using the ARDL Bounds approach to cointegration, we explore the role of financial services, information and communications technology, remittance inflows and export liberalisation in Nepal over the periods 1975-2010 (36 years). The results show that financial development, ICT, remittance inflows and openness are instrumental in improving income level both in the longrun. Positive outcomes are also noted in the short-run with exception of negative lagged effects. Consequently, besides the need for stable macroeconomic policies and effective institutional structures, policies need to be focused on: greater financial and technology integration, investment in and integration of technology and innovation across sectors, encouraging greater remittance inflows through with proper labour mobility schemes, export promotion strategies not only addressing supply side constraints but also strengthening trade partnership at regional and international level.The Economic Journal of Nepal, Vol. 34, No. 1, January - March 2011 (Issue N0. 133)Uploaded date: 3/27/2014